Cerebral blood flow velocity progressively decreases with increasing levels of verticalization in healthy adults. A cross-sectional study with an observational design - Deseoe, Julian; Schwarz, Anne; Pipping, Theodor; Lehmann, Aurelia; Veerbeek, Janne M.; Luft, Andreas R.; Wegener, Susanne; Globas, Christoph; Held, Jeremia P. O. (Frontiers in Neurology, 2023)
Background: Autoregulation of the cerebral vasculature keeps brain perfusion stable over a range of systemic mean arterial pressures to ensure brain functioning, e.g., in different body positions. Verticalization, i.e., transfer from lying (0°) to upright (70°), which causes systemic blood pressure drop, would otherwise dramatically lower cerebral perfusion pressure inducing fainting. Understanding cerebral autoregulation is therefore a prerequisite to safe mobilization of patients in physiotherapy. Aim: We measured the impact of verticalization on cerebral blood flow velocity (CBFV) and systemic blood pressure (BP), heart rate (HR) and oxygen saturation in healthy individuals. Method: We measured CBFV in the middle cerebral artery (MCA) of the dominant hemisphere in 20 subjects using continuous transcranial doppler ultrasound (TCD). Subjects were verticalized at 0°, -5°, 15°, 30°, 45° and 70° for 3-5 min each, using a standardized Sara Combilizer chair. In addition, blood pressure, heart rate and oxygen saturation were continuously monitored. Results: We show that CBFV progressively decreases in the MCA with increasing degrees of verticalization. Systolic and diastolic BP, as well as HR, show a compensatory increase during verticalization. Conclusion: In healthy adults CBFV changes rapidly with changing levels of verticalization. The changes in the circulatory parameters are similar to results regarding classic orthostasis.